OS2.5 Effect of rituximab in primary central nervous system lymphoma - results of the randomized phase III HOVON 105/ALLG NHL 24 study. (19th September 2018) - Bromberg, J E C; Issa, S; Bakunina, K; Minnema, M C; Seute, T; Cull, G; van den Bent, M J; Gonzales, M; de Jong, D; Doorduijn, J K
Abstract: Background: use of rituximab in Primary Central Nervous System Lymphoma (PCNSL) is based on extrapolation of its impact on survival rates in systemic diffuse large B-cell lymphoma and phase II and retrospective PCNSL studies. We performed an international intergroup randomized phase III study to investigate efficacy of rituximab in PCNSL. Material and Methods: newly-diagnosed, non-immunocompromized patients aged 18–70 years with PCNSL and WHO performance status (PS) 0–3 were randomized to induction with 2 cycles of MBVP chemotherapy with (arm B) or without (arm A) rituximab. Patients were stratified for age (≤60 vs ≥61 years) and PS (0–1 vs 2–3). Rituximab (375 mg/m 2 ) was given weekly during MBVP cycle I and every other week during cycle II to a total of 6 administrations. Patients with persistently positive CSF after the first (R-)MBVP cycle received intrathecal MTX; those with at least a partial response received high dose cytarabine consolidation. Patients ≤ 60 years were then consolidated with 30 Gy whole brain radiotherapy (WBRT) with an additional boost of 10 Gy in case of partial remission (PR). Patients ≥61 yrs were not irradiated. Primary end-point was one year event free survival (EFS), where an event was no CR(u) on protocol, relapse or death. Secondary end-points were response rates after induction, consolidation and completion of WBRT, PFS and OS. Results: between August 2010 and June 2016, 200 patients from 24 centers in the Netherlands, Australia and New Zealand were included and randomized; 100 patients to arm A and 99 to arm B, 1 was not eligible and excluded from all analyses. 55% were men. The median age was 61 years (range 26–70), 47% were ≤60 years, 72% had an ECOG PS ≤ 1, 29% had elevated LDH and 30% had positive CSF; the two arms were well balanced at baseline. All patients received cycle I according to randomization, 90% received cycle II and 81% received high dose cytarabine. 16 patients, 8 in each arm, received intrathecal treatment. 70 patients (35%) were irradiated, 34% in arm A and 36% in arm B. A boost was given to 15/34 patients in arm A (44%) and 24/36 patients in arm B (67%). CR/CRu rate was 66% in arm A and 68% in arm B. Overall Response Rate was 87% in both arms. EFS did not differ between the arms: 1 year EFS was 49% in arm A and 52% in arm B; HR 1.00, 95% CI 0.70–1.43, p=0.99 adjusted for age group and WHO. Median OS has not been reached after a median follow-up of 32.9 months (range 3.6–79.2) in the 120 patients still alive but no difference was apparent with an adjusted analysis HR of 0.93 (95% CI 0.59 - 1.44, p=0.74). At database lock 79 patients had died; treatment related mortality was 7% in arm A and 3% in arm B. Grade 3 or 4 adverse events occurred in 59% of patients in arm A, in 63% in arm B. Conclusion: addition of rituximab to HD-MTX-based chemotherapy did not improve response rates, EFS or PFS in PCNSL.